If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -5)(x + -5) = 0 Reorder the terms: 2(-5 + x)(x + -5) = 0 Reorder the terms: 2(-5 + x)(-5 + x) = 0 Multiply (-5 + x) * (-5 + x) 2(-5(-5 + x) + x(-5 + x)) = 0 2((-5 * -5 + x * -5) + x(-5 + x)) = 0 2((25 + -5x) + x(-5 + x)) = 0 2(25 + -5x + (-5 * x + x * x)) = 0 2(25 + -5x + (-5x + x2)) = 0 Combine like terms: -5x + -5x = -10x 2(25 + -10x + x2) = 0 (25 * 2 + -10x * 2 + x2 * 2) = 0 (50 + -20x + 2x2) = 0 Solving 50 + -20x + 2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(25 + -10x + x2) = 0 Factor a trinomial. 2((5 + -1x)(5 + -1x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Subproblem 2
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Solution
x = {5, 5}
| xx-2x+1=0 | | (3d-7)+8=0 | | 7/4u=1/2-1/6v | | y+-4y=118 | | 5x-(17*13)/122=2 | | (6y+5)+(2y-6)=118 | | (6y+5)+(2y-6)= | | 1x+20+2x=-10-2x-15 | | 16x+8x=192 | | 9+3x=14+2x | | (1800+x)/(25+y)=80 | | (3y+5)+(y-6)=118 | | 10cos(10x)=0 | | (-(-3x-5y)/4x)-((4x+9y)/4x)=0 | | 8x+4x=192 | | (7x+1)-(x-5)=6 | | 7x+1-5x=6 | | 2.5=(540-x)/x | | x+raiz(x-1)=13 | | 2.5X=540-x | | 2.5X=240-X | | y=14x^2-56 | | 2/3x+12=8 | | x-5/2x+15=0 | | 18(0.5)/x=3 | | x-4x+9=0 | | x-4x+8=0 | | x-1/5x-20=0 | | 7x+15/4=8 | | (5x/6)+2=(3x/4) | | e-3/5=6 | | 4i/5=12 |